Formation And Development Of Cognitive Processes In Preschool Children - Oymatova Dilorom Ruzimurotovna; Omonova Shokhista Anvar qizi; Rakhimova Durdona Murot qizi (Euro Asian Journal Publishing, 2025)
This article analyzes the development characteristics of cognitive processes in preschool children — sensation, attention, perception, memory, imagination, thinking, and speech. The interrelation of these mental processes and their significance in the pedagogical process are examined from a scientific perspective. The article is enriched with modern psychological approaches and practical recommendations
Keywords: cognitive processes; sensation; attention